The unrealised ethical potential of the Methodist theology of prevenient grace - Field, David (HTS teologiese studies, 2015)
This article examines the unrealised ethical potential of the theology of prevenient grace. It begins with a brief analysis of John Wesley’s rejection of slavery as rooted in his theology of prevenient grace. This is demonstrated in the next section which analyses Wesley’s notion of prevenient grace. This is followed by a constructive proposal for a contemporary theology of prevenient grace and some ethical implications of this theology, for contemporary social and political ethics, are developed.